2007
DOI: 10.1021/bm060877b
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Domain Orientation on the Mechanical Properties of Regenerated Cellulose Fibers

Abstract: The determination of the crystal orientation of regenerated cellulose fibers produced under different drawing regimes is presented. Orientation is determined by using wide-angle X-ray diffraction from a synchrotron source and by measuring the azimuthal width of equatorial reflections. The orientation parameter theta is then determined to compare fiber samples. By using a 500 nm beam size, clear differences between the crystal orientations of the skin and the core of the fibers are reported for a range o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 21 publications
1
20
0
Order By: Relevance
“…Furthermore, the reduction in the sharpness of the reflections for the composites prepared with longer immersion time also indicates lower molecular orientations in these composites. This is caused by an increase in the fraction of the formed amorphous phase (no orientation) with immersion time [32]. Correspondingly, the scanning electron micrographs (SEM) of the cross-section of the composites ( Figure 5) show that longer immersion times lead to a reduction in fibre size and the formation of thicker matrix layers between the remaining fibre cores.…”
Section: Resultsmentioning
confidence: 91%
“…Furthermore, the reduction in the sharpness of the reflections for the composites prepared with longer immersion time also indicates lower molecular orientations in these composites. This is caused by an increase in the fraction of the formed amorphous phase (no orientation) with immersion time [32]. Correspondingly, the scanning electron micrographs (SEM) of the cross-section of the composites ( Figure 5) show that longer immersion times lead to a reduction in fibre size and the formation of thicker matrix layers between the remaining fibre cores.…”
Section: Resultsmentioning
confidence: 91%
“…That is, flax,2, 3 coir,4 thin slices of wood,3, 5, 6 and single wood fibers5 using X‐ray diffraction (XRD) technique. Wide‐angle XRD experiments with strained regenerated cellulose fibers7–9 and cellulose composite films10 also demonstrated the reorientation of crystalline regions upon straining. In a recent study, it was shown that the mechanical performance of regenerated cellulose films can be greatly improved by stretching in wet condition and consecutive drying 11…”
Section: Introductionmentioning
confidence: 95%
“…However, Gindl et al (2006) showed that only two different parts within lyocell fiber do exist, skin and core. They observed that studied fibers have uniform skin-core orientation, in contrast, Kong et al (2007) obtained non-uniform skin-core orientation by X-ray diffraction as claimed due to the differences of used beam size (5 × 5 µm vs. 500 nm). This non-uniformity resulted in the higher average orientation of the fiber skin than of the core.…”
Section: Regenerated Cellulosementioning
confidence: 91%